2016
DOI: 10.3823/1924
|View full text |Cite
|
Sign up to set email alerts
|

Evidence For Dry Eye Treatment In Hematopoietic Stem Cells Post-Transplantation

Abstract: Introduction: Hematopoietic Stem Cell Transplantation (HSCT) is a treatment modality for oncology and hematological diseases genetically inherited or acquired. The morbidities and mortalities related to HSCT are evident in its different phases, such as the Graft Versus Host Disease especially on dry eye syndrome, one of the most complication of chronic phase, characterized as a multifactorial disease of the ocular surface. Several treatments may be directed to the dry eye and the consequences caused by it duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 50 publications
(27 reference statements)
0
2
0
Order By: Relevance
“…Many patients with oGVHD suffer from severe ocular complications resulting in impairment of vision and quality of life 10 , 11 . The management of vision-threatening complications associated with oGVHD is often challenging 7 , 19 21 . Although previous studies on chronic oGVHD have reported clinical manifestations and associated risk factors 2 , 4 , 5 , 22 24 ; some of these studies examined only one of the severe ocular manifestations, such as PED and corneal perforation 9 , 18 , 25 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many patients with oGVHD suffer from severe ocular complications resulting in impairment of vision and quality of life 10 , 11 . The management of vision-threatening complications associated with oGVHD is often challenging 7 , 19 21 . Although previous studies on chronic oGVHD have reported clinical manifestations and associated risk factors 2 , 4 , 5 , 22 24 ; some of these studies examined only one of the severe ocular manifestations, such as PED and corneal perforation 9 , 18 , 25 .…”
Section: Discussionmentioning
confidence: 99%
“…The management of vision-threatening complications associated with oGVHD is often challenging, due to severe inflammation, lack of vital components to maintain ocular surface homeostasis, and poor systemic condition 7 , 19 21 . Identification of risk factors associated with oGVHD severity and poor vision outcomes may support the clinical management of affected patients.…”
Section: Introductionmentioning
confidence: 99%